2014
DOI: 10.1111/mmi.12634
|View full text |Cite
|
Sign up to set email alerts
|

Specific domains of plant defensins differentially disrupt colony initiation, cell fusion and calcium homeostasis in Neurospora crassa

Abstract: SummaryMsDef1 and MtDef4 from Medicago spp. are small cysteine-rich defensins with potent antifungal activity against a broad range of filamentous fungi. Each defensin has a hallmark γ-core motif (GXCX3-9C), which contains major determinants of its antifungal activity. In this study, the antifungal activities of MsDef1, MtDef4, and peptides derived from their γ-core motifs, were characterized during colony initiation in the fungal model, Neurospora crassa. These defensins and their cognate peptides inhibited c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 61 publications
2
44
0
4
Order By: Relevance
“…However, PAF D19S acted fungicidal in a time dependent manner when applied at its MEC (32 μM) suggesting that fungal killing is mediated by other motifs that regulate mechanisms independently from the elevation of [Ca 2+ ] c . Our observation parallels with recent studies on plant defensins: by using defensin fragments amino acid sequences were identified that exhibit distinct antifungal features of their parental proteins [28]. …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, PAF D19S acted fungicidal in a time dependent manner when applied at its MEC (32 μM) suggesting that fungal killing is mediated by other motifs that regulate mechanisms independently from the elevation of [Ca 2+ ] c . Our observation parallels with recent studies on plant defensins: by using defensin fragments amino acid sequences were identified that exhibit distinct antifungal features of their parental proteins [28]. …”
Section: Discussionsupporting
confidence: 88%
“…The specificity of the interference with divalent cations is further corroborated by the observation that monovalent cations like Na + had no/little effect on the antifungal activity of PAF and PAF D19S . Whereas the role of Mg 2+ ions in the activity of antifungal proteins awaits further investigations, the relevance of Ca 2+ ions in the mechanistic function of PAF and other related antifungal proteins and peptides was studied in detail [23,28,31,38] and let assume that their role goes beyond the disruption of electrostatic interactions. We assume that Ca 2+ ions may influence the PAF-response of the sensitive fungus in one or more of the following ways: (i) competition with PAF for binding to a Ca 2+ -sensitive interaction molecule, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different mechanisms of action of defensins can be explained by the variable primary sequences; the major determinants of the antifungal and morphogen activities of defensins reside in their g-core motifs [18,30]. MsDef1 (defensin 1.3 of M. sativa) and MtDef4 each contain a conserved g-core structural motif (GXCX 3-9 C, where X is any amino acid), which is a hallmark signature of disulfide-stabilized antimicrobial peptides [31].…”
Section: Truncatula Defensinsmentioning
confidence: 99%
“…Heterologous overexpression of various PDFs leads to increased resistance of both model plants and crops against different fungi and bacteria (Carvalho Ade and Gomes, 2011;De Coninck et al, 2013b;Gaspar et al, 2014). The modes of action of several PDFs, including radish (Raphanus sativus) AFP2, Nicotiana alata D1, alfalfa (Medicago sativa) Def1, M. truncatula Def4, and pea (Pisum sativum) d1, have been well studied and point toward specific interactions with various fungal sphingolipids and phospholipids (Thevissen et al, 2004(Thevissen et al, , 2012Aerts et al, 2007;Lobo et al, 2007;Ramamoorthy et al, 2007;van der Weerden et al, 2008van der Weerden et al, , 2010Sagaram et al, 2011Sagaram et al, , 2013Muñoz et al, 2014). Upon interaction, PDFs are either internalized by the fungal cell and interact with intracellular targets, or they stay outside the cell and induce cell death through induction of a signaling cascade (Vriens et al, 2014).…”
Section: Cysteine-rich Peptidesmentioning
confidence: 99%